Jinadatta Suri probably show he saved a drowning ship - Temples of India Project Team (Jio Institute, 2024)
The story in the sixteenth oval painting (in clockwise order) in the lower/outer circle in the ceiling of the mandapa (pillared hall) revolves around Jinadatta Suri, probably depicting how he saved a drowning ship. The acharya (those who impart knowledge) is sitting on the banks of the water body, accompanied by three disciples. The ship in the water has an elephant head, and a person in Rajasthani attire is seated on the ship. The water contains aquatic flora and fauna, such as fish and lotus flowers. The inscription reads, ‘Shri Jinadatta Suri ji ne nevai dari.’ The most interesting aspect of this painting is the name of the artist, M. Altaf, inscribed at the bottom of the oval border of the painting.